A Rare Truncating BRCA2 Variant and Genetic Susceptibility to Upper Aerodigestive Tract Cancer - Delahaye-Sourdeix, Manon; Anantharaman, Devasena; Timofeeva, Maria N.; Gaborieau, Valérie; Chabrier, Amélie; Vallée, Maxime P.; Lagiou, Pagona; Holcátová, Ivana; Richiardi, Lorenzo; Kjaerheim, Kristina; Agudo, Antonio; Castellsagué, Xavier; et al. (JNCI : Journal of the National Cancer Institute, 2015)
Deleterious BRCA2 genetic variants markedly increase risk of developing breast cancer. A rare truncating BRCA2 genetic variant, rs11571833 (K3326X), has been associated with a 2.5-fold risk of lung squamous cell carcinoma but only a modest 26% increase in breast cancer risk. We analyzed the association between BRCA2 SNP rs11571833 and upper aerodigestive tract (UADT) cancer risk with multivariable unconditional logistic regression adjusted by sex and combinations of study and country for 5942 UADT squamous cell carcinoma case patients and 8086 control patients from nine different studies. All statistical tests were two-sided. rs11571833 was associated with UADT cancers (odds ratio = 2.53, 95% confidence interval = 1.89 to 3.38, P = 3x10(-10)) and was present in European, Latin American, and Indian populations but extremely rare in Japanese populations. The association appeared more apparent in smokers (current or former) compared with never smokers (P het = .026). A robust association between a truncating BRCA2 variant and UADT cancer risk suggests that treatment strategies orientated towards BRCA2 mutations may warrant further investigation in UADT tumors.